2017
DOI: 10.1016/j.jvs.2016.10.081
|View full text |Cite
|
Sign up to set email alerts
|

Basilic elevation transposition may improve the clinical outcomes for superficialization of basilic arteriovenous fistula veins

Abstract: BET is a reliable approach that yields a high cumulative fistula survival rate. Compared with BTT, BET is associated with improved basilic vein primary patency and reduced need for endovascular interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 29 publications
(92 reference statements)
2
25
0
3
Order By: Relevance
“…During the maturation process of some AVFs, elongation can occur in addition to dilation. While we did not encounter any significant elongation in our cohort, moderate straightening can be performed with this technique by orienting the outflow vein at the most lateral aspect of the skin flap or creating a lateral pouch, if necessary, as described by Wang et al 6 for their basilic elevation transposition technique. If there is excessive length, part of the excess vein can be resected and an end-to-end anastomosis can be created.…”
Section: Surgical Techniquementioning
confidence: 73%
“…During the maturation process of some AVFs, elongation can occur in addition to dilation. While we did not encounter any significant elongation in our cohort, moderate straightening can be performed with this technique by orienting the outflow vein at the most lateral aspect of the skin flap or creating a lateral pouch, if necessary, as described by Wang et al 6 for their basilic elevation transposition technique. If there is excessive length, part of the excess vein can be resected and an end-to-end anastomosis can be created.…”
Section: Surgical Techniquementioning
confidence: 73%
“…Wang et al recently compared two-stage elevation with two-stage transposition and found that two-stage elevation is a reliable approach because of better primary patency and reduced need for salvage interventions to the fistulas. 36 ) The interval between the first and second operations is varied from 3 to 8 weeks depending on the maturation criteria of the basilic vein.…”
Section: Surgical Techniquementioning
confidence: 99%
“…A basilic vein transposition elevation procedure in the upper arm was performed as previously described. 4,5 All vein branches were ligated and divided while fibers of the median cutaneous nerve were gently separated longitudinally to allow elevation of the vein into a superficial position, anterior to the incision. 6 A video of the vein elevation procedure is available for review.…”
Section: Technical Notementioning
confidence: 99%
“…We report our successful use of basilic vein transposition in the upper arm as an option for establishing a safe and functional access while preserving the advantages of a distal wrist anastomosis and offering a larger access target with a much more reliable location for AVF cannulation. 4…”
Section: Introductionmentioning
confidence: 99%